Efficacy of a mobile phone-based intervention on health behaviors and HIV/AIDS treatment management: randomized controlled trial - Tran, Bach Xuan (2023)
Background: Antiretroviral therapy (ART) is considered the most important intervention for HIV-positive patients; thus, encouraging the use of and adherence to ART are vital to HIV treatment outcomes. Advances in web and mobile technologies hold potential in supporting HIV treatment management. Objective: The aim of this study was to evaluate the feasibility and efficacy of a theory-based mobile health (mHealth) intervention on health behaviors and HIV treatment adherence among patients with HIV/AIDS in Vietnam. Methods: We performed a randomized controlled trial on 425 HIV patients in two of the largest HIV clinics in Hanoi, Vietnam. Both the intervention group (238 patients) and the control group (187 patients) received regular consultations with doctors and then participated in 1-month and 3-month follow-up visits. Patients in the intervention group received a theory-driven smartphone app to facilitate medication adherence and self-efficacy in HIV patients. Measurements were developed based on the Health Belief Model, which included the visual analog scale of ART Adherence, HIV Treatment Adherence Self-Efficacy Scale, and HIV Symptom Management Self-Efficacy Scale. We also included the 9-item Patient Health Questionnaire (PHQ-9) to assess patients’ mental health throughout treatment. Results: In the intervention group, the adherence score increased significantly (β=1.07, 95% CI .24-1.90) after 1 month, whereas the HIV adherence self-efficacy was significantly higher after 3 months (β=2.17, 95% CI 2.07-2.27) compared to the control group. There was a positive but low level of change in risk behaviors such as drinking, smoking, and drug use. Factors related to positive change in adherence were being employed and having stable mental well-being (lower PHQ-9 scores). Factors associated with self-efficacy in treatment adherence and symptom management were gender, occupation, younger age, and having no other underlying conditions. A longer duration of ART increased treatment adherence but decreased self-efficacy in symptom management. Conclusions: Our study demonstrated that the mHealth app could improve the overall ART adherence self-efficacy of patients. Further studies with larger sample sizes and longer follow-up periods are needed to support our findings.